Pengaruh Edukasi Gizi Melalui Media Buku Cerita Terhadap Pengetahuan, Sikap dan Perilaku Konsumsi Sayur dan Buah Anak Kelas 5 SDIT Thariq Bin Ziyad Tahun 2019 - Annisa - Fitryadi (Universitas Harapan Bangsa Purwokerto, 2020)
Nutritional problems in the community, especially among children, are lack of consumption of vegetables and fruit, as many as 93.6% of the Indonesian population of children aged ≥10 years are still consuming less vegetables and fruits, while the prevalence in West Java was obtained by 96.4% of the Indonesian population consuming less vegetables and fruits, this study aims to determine the effect of nutritional education through storybook media on the knowledge, attitudes and behavior of vegetable and fruit consumption in 5th grade children of SDIT Thariq bin Ziyad in 2019. The study design was a quasi-experiment design with a non-randomized one group pretest-posttest. The research subjects consisted of 33 students as the intervention group. The research subjects consisted of 33 students as a treatment group and a control group. The media used is story books. The results of bivariate analysis with the Wilcoxon Test Rank Test showed the knowledge of the intervention group (p = 0.002 (<0.05)), the attitude of the intervention group (p = 0,000 (<0, 05)) and the consumption behavior of the intervention group (p = 0,000 (<0.05)). This means that there are influences before and after the provision of nutritional education with storybook media on the knowledge, attitudes and behavior of vegetable and fruit consumption in 5th grade children as an intervention group.